Optimization of treatment efficiency of UV/H2O2 process on simulated textile industry wastewater. Issue 56 (1st December 2016) - Manikandan, P.; Palanisamy, P.N.; Baskar, R.; Sivakumar, P.; Sakthisharmila, P.
Abstract: The present study involves optimization of UV/H2 O2 process on a simulated dye bath effluent by varying initial H2 O2 concentration, pollution load, and pH. The process was optimized by four factors and three levels of Box–Behnken design coupled with response surface methodology. During the experiment, color removal and degradation studies were also performed to ensure the treatment efficiency. The results obtained show that the color removal efficiency can be achieved within a short time due to the degradation of the structure which is more susceptible to oxidation. Then slower and gradual degradation of the simple and conjugated aromatic compounds takes place. In the first 5 min of the irradiation of the dyes, the pH value decreased from 11 to 9.5 and for another pH value decreased from 9 to 7.01. The drop in the pH value is mainly due to the formation of organic as well as inorganic acid as a degradation product. Under the optimum operating conditions such as pollution load of 64%, initial concentration of H2 O2 0.6 M, initial pH 8, and treatment time of 81 min the predicted removal efficiencies are 98.77 and 86.11% for Color removal and COD removal, respectively.